The Use of Marine Algae as a Denture Cleanser: A Narrative Review - Manivasakan, Shivasakthy; Roopa, Gogula Sree; Livingstone, David (Research Perspectives of Microbiology and Biotechnology Vol. 6, 2024)
Denture usage is increasing in the geriatric society, and denture stomatitis is one of the problems faced by the majority of denture wearers. Denture stomatitis is not merely a result of Candida albicans; it is formed by a biofilm of various species. Several mechanical and chemical methods have been employed, and many studies have tested the antifungal properties of commercially available denture cleansers and other agents such as coconut oil and eucalyptus oil. Marine bioactive products like seaweed have also been used. The brown seaweed Sargassum polycystum and Turbinaria conoides have antifungal and antibacterial activity. There is a need for further studies to be conducted to evaluate the efficacy of the seaweeds available.